Cross-Metathesis Coupling for Access to Some New α,β-Unsaturated Esters Derived from 2-Mercaptobenzoxazole - Dawood, Rafid S. (Iraqi Journal of Science, 2025)
This study involves the synthesis of eight α,β-unsaturated ester compounds, obtained from 2-mercaptobenzoxazoles 3-10 by a two-step reaction. The first step included S-allylation of 2-mercaptobenzoxazole (1) with allyl bromide to furnish 2-(allylthio)benzo[d]oxazole (2) in a good yield (71%). The second step involved a cross-metathesis reaction of compound 2 with acrylate esters, which afforded the title products 3-10 in yields between 70 and 86%. The structure of the prepared compounds (2-10) was confirmed by FT-IR, 1H NMR, and 13C NMR spectroscopy.